Kajian Semantik Aspek Gramatikal dan Leksikal pada Lirik Lagu Membasuh Karya Hindia - Andreansyah, Vicky Ivan; Wahyono, Hari (Kajian Bahasa dan Sastra (KABASTRA), 2025)
Song lyrics have various meanings, one of which is the outpouring of a lyricist which is expressed in written words and can influence the emotions and feelings of song listeners. This study aims to describe the grammatical and lexical aspects of the lyrics of the song Membasuh by Hindia using semantic studies. The research method applied in this study is a qualitative descriptive method that produces descriptive data in the form of words. The data obtained came from the lyrics of the song entitled Membasuh by Hindia. This study focused on the grammatical and lexical aspects of the lyrics of the song Membasuh by Hindia. The data collection method in this study was carried out using the documentation and note-taking method. This study found that in the lyrics of the song Membasuh by Hindia there are grammatical aspects consisting of reference, ellipsis, and conjunction. While the lexical aspects found consist of repetition, synonyms, and antonyms.